The Readiness and Willingness of Thai Professional Accountants towards their Working in ASEAN: Problems and Solutions for Preparedness - ติรศรีวัฒน์, อมรา (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2018)
This research aims to study the readiness and willingness of Thai professional accountants towards their working in ASEAN member countries. Questionnaire was used as tool for collecting data from 390 professional accountants who work in international and Certified Thai Accounting Practice in Thailand. The collected data was analyzed in terms of percentage, means, ranking, priority need index (PNI) assessment, analysis of comments and reasons for their decision making. The motivation of persons who are ready and willing for mobility are a higher remuneration, better profile from experience at an international level, and more opportunity for travelling and networking. Professional accountants who are ready but not willing to work in AEC due to personal and family problems i.e. burden and responsibility to members in the family, social and political involve risk and insecurity in host country. In addition, professional accountants who are not ready to work in ASEAN but they are willing to go in the future due to problems of English proficiency as the most important, and also lack of communication skills in both English and local languages, lack of qualifications desired by original and host countries. The highest possibility and potentiality of accounting career for mobility of Thai professional accountants to work in AEC are Financial Accountants due to the least restriction and regulation of its professions in both origin and host country.